TANGGUNG JAWAB PENGURUS KOPERASI MITRA MULTI PERKASA ATAS KETERLAMBATAN DALAM PENGIRIMAN SAWIT MILIK PT. FAJAR SAUDARA KUSUMA DI KABUPATEN SAMBAS - NIM. A1011141128, GERY AKBAR (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac In this case, the delivery agreement is in the form of oral, this agreement has occurred when an agreement is reached between the parties who entered into the agreement. The delivery agreement which is made legally after fulfilling the provisions in article 1320 of the Civil Code, applies as law for those who make it; the parties are bound to carry out the agreement. The formulation of the problem became